Information and Communication Technology (ICT) Integration: A Veritable Technique for Quality Secondary Education - Bolaji, Hammed Olalekan; Ajia, Ismaeel Saka (Bumi Publikasi Nusantara, 2023)
Information and communication technology (ICT) is an indispensable tool for teachers to meet the global expectation of modern teaching techniques with the use of technology-based teaching and learning tools and facilities. This paper examines how schools can best integrate Information Communication, and Technology to support the teaching and learning process in the classroom and enhance quality secondary school education. Some of the problems that serve as obstructs in the wheel of quality education system include inadequate funding, lack of readiness, human readiness, system readiness, physical readiness, and teacher awareness, knowledge, and understanding of the benefits of ICTs in the effective management of secondary education among others in Nigeria. The Nigerian government is the primary driver of ICTs for education in Nigeria and other ICT providers as Donors. Some identified factors for the effective use of ICT were detailed and the greatest obstacle to technology use in secondary schools is a lack of readiness. Solutions to those challenges were enlisted among others are the planning process of integration of ICT should involve all stakeholders and national action plans must take cognizance of local constraints and salient educational needs. It was recommended among others that teachers should use ICT with students to collaborate with their peers and provide a high-quality education.